Development and validation of a rapid RP-HPLC method for the determination of cetirizine or fexofenadine with pseudoephedrine in binary pharmaceutical dosage forms - KARAKUŞ, SEVGİ (ELSEVIER SCIENCE BV, 2008)
The objective of the current study was to develop a simple, accurate, precise and rapid reversed-phase HPLC method and subsequent validation using ICH suggested approach for the determination of antihistaminic-decongestant pharmaceutical dosage forms containing binary mixtures of pseudoephedrine hydrochloride (PSE) with fexofenadine hydrochloride (FEX) or cetirizine dihydrochloride (CET). The chromatographic separation of PSE, FEX and CET was achieved on a Zorbax C8 (150 mm x 4.6 mm; 5 mu m particle size) column using UV detection at 218 and 222 nm. The optimized mobile phase was consisted of TEA solution (0.5%, pH 4.5)-methanol-acetonitrile (50:20:30, v/v/v). The retention times were 1.099, 2.714 and 3.808 min for PSE, FEX and CET, respectively. The proposed method provided linear responses within the concentration ranges 30-240 and 1.25-10 mu g ml(-1) with LOD values of 1.75 and 0. 10 mu g ml(-1) for PSE and CET, respectively. Linearity range for PSE-FEX binary mixtures were 10-80 and 5-40 mu g ml(-1) with LOD values of 0.75 and 0.27 mu g ml(-1) for PSE and FEX, respectively. Correlation coefficients (r) of the regression equations were greater than 0.999 in all cases. The precision of the method was demonstrated using intra- and inter-day assay R.S.D. values which were less than 1% in all instances. No interference from any components of pharmaceutical dosage forms or degradation products was observed. According to the validation results, the proposed method was found to be specific, accurate, precise and could be applied to the quantitative analysis of these drugs in capsules containing PSE-CET or extended-release tablets containing PSE-FEX binary mixtures. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: cetirizine; fexofenadine; pseudoephedrine; reversed-phase HPLC; validation; LIQUID-CHROMATOGRAPHIC DETERMINATION; SEASONAL ALLERGIC RHINITIS; HUMAN PLASMA; CAPILLARY-ELECTROPHORESIS; DERIVATIVE SPECTROPHOTOMETRY; PHARMACOLOGICAL PROPERTIES; HYDROCHLORIDE; DIHYDROCHLORIDE; TABLETS; FORMULATIONS